2016
DOI: 10.1093/mnras/stw338
|View full text |Cite
|
Sign up to set email alerts
|

nIFTY galaxy cluster simulations – III. The similarity and diversity of galaxies and subhaloes

Abstract: The version presented here may differ from the published version or from the version of the record. Please see the repository URL above for details on accessing the published version and note that access may require a subscription.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 122 publications
2
38
0
Order By: Relevance
“…The galaxies also differ due to the varying treatment of baryonic processes, as seen in e.g. Sembolini et al (2016a,b); Elahi et al (2016); Cui et al (2016b); Arthur et al (2017). Note that the galaxy positions are identical for the two SAMs as they reflect the positions of the dark matter haloes in the underlying dark-matter-only simulation which are the same.…”
Section: Cluster Bulk Propertiesmentioning
confidence: 92%
“…The galaxies also differ due to the varying treatment of baryonic processes, as seen in e.g. Sembolini et al (2016a,b); Elahi et al (2016); Cui et al (2016b); Arthur et al (2017). Note that the galaxy positions are identical for the two SAMs as they reflect the positions of the dark matter haloes in the underlying dark-matter-only simulation which are the same.…”
Section: Cluster Bulk Propertiesmentioning
confidence: 92%
“…Simulations are run from redshift 120 to redshift zero. Note that the N-body code used in this paper is different from that used in our previous papers (e.g Sorce et al 2016b) for two reasons: 1) results obtained with two different N-body code are supposed to be similar in the dark matter only case (Elahi et al 2016). We check that this is indeed the case for our constrained simulations ; 2) in a perspective of hydrodynamical simulations of the Virgo cluster, the adaptive mesh refinement grid code will be used.…”
Section: Simulationsmentioning
confidence: 96%
“…GadgetX, equipped with these subgrid schemes, has been extensively tested by the Trieste numerical group (Rasia et al 2015;Planelles et al 2017;Biffi et al 2017) and in the nIFTy cluster comparison project (Sembolini et al 2016b;Elahi et al 2016;Cui et al 2016;Arthur et al 2017). These latter studies have shown that GadgetX was able to produce a realistic and stable M200 = 1.1 x 10 15 h −1 M cluster at z = 0, using a similar particle mass resolution as used in TheThreeHundred project.…”
Section: Hydrodynamical Codementioning
confidence: 99%